2005
DOI: 10.1037/0022-3514.89.5.657
|View full text |Cite
|
Sign up to set email alerts
|

Priming a New Identity: Self-Monitoring Moderates the Effects of Nonself Primes on Self-Judgments and Behavior.

Abstract: When a construct is primed, people often act in construct-consistent ways. Several accounts for this effect have been offered, including ideomotor theory and a social functional perspective. The authors tested an additional perspective, the Active-Self account, whereby primes can temporarily alter self-perceptions. In Study 1, non-African American participants reported feeling more aggressive on an implicit measure following an African American prime. In Study 2, participants reported feeling luckier on an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
3
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(169 citation statements)
references
References 89 publications
(187 reference statements)
8
155
3
2
Order By: Relevance
“…Finally, participants completed an implicit threat measure used in previous studies (DeMarree, Wheeler, & Petty, 2005). We used an implicit measure because individuals are not always forthcoming about the level of threat they experience (Hass, Katz, Rizzo, Bailey, & Moore, 1992).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, participants completed an implicit threat measure used in previous studies (DeMarree, Wheeler, & Petty, 2005). We used an implicit measure because individuals are not always forthcoming about the level of threat they experience (Hass, Katz, Rizzo, Bailey, & Moore, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…To create an overall measure of threat of status loss, we computed a composite measure by summing the number of threat related words selected. Scores ranged from 0 to 6; higher scores indicated a stronger feeling of threat of status loss (DeMarree et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Relevant to our claims, Hassin et al argued that the Israeli flag expressed the ideal of national unity, thereby priming participants to adopt a more moderated stance toward Palestinians. Other, now-classic priming studies have shown that people tend to adopt the slow gait typical of an elderly person (Bargh et al, 1996), the cognitive styles of a professor or hooligan (Dijksterhuis & van Knippenberg, 1998), or the stereotypes associated with other outgroups (DeMarree, Wheeler, & Petty, 2005; see also the active-self account of Wheeler & Petty, 2001) when primed with concepts related to those groups. In all cases, these primes were well known to participants, and participants responded by adopting the cognitive styles associated with those primes.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Other studies have shown that the Proteus effect also applies to fully embodied VR; Freeman et al (2014) showed that embodying a short avatar led to more negative self-evaluation and greater feelings or paranoia, while Rosenberg, Baughman, and Bailenson (2013) showed that, after embodying an avatar with the superhero-like power of flight, participants displayed greater pro-social behaviour. Interestingly, although the Proteus effect was designed to explain the effects of using virtual avatars in computer games, there is evidence that any cognitive processing that activates stereotypes about others can lead to stereotypes about the other being transferred onto the self (DeMarree, Wheeler, & Petty, 2005;Kawakami et al, 2012;Wheeler, Demarree, & Petty, 2007).…”
Section: Future Directions: Changing Attitudes Via Embodiment Outsidementioning
confidence: 99%